2020
DOI: 10.20538/1682-0363-2019-4-119-126
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the CYP2C19*17 genetic polymorphism and the efficacy and safety of diazepam in patients with alcohol withdrawal syndrome

Abstract: The aim of our study was to study the relationship between the CYP2C19 genetic polymorphism and the efficacy and safety of diazepam in patients with alcohol withdrawal syndrome in order to develop algorithms for optimizing the therapy of diazepam to reduce the risk of dose-dependent adverse drug reactions and pharmacoresistance.Materials and methods. The study was conducted on 30 Russian male patients suffering from alcohol withdrawal syndrome. For the treatment of anxiety, fear and emotional tension, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…These results are consistent with the findings of our previous study focused on investigation of the CYP2C19*2 genetic polymorphism, which had a 2-times lower sample size and enrolled 50 patients [7]. Furthermore, previous studies which were conducted by our research group [14,15], confirm the importance, relevance and possibility to investigate the personalized approach to the prescription of BZDs (and specifically diazepam) in such cohort of patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with the findings of our previous study focused on investigation of the CYP2C19*2 genetic polymorphism, which had a 2-times lower sample size and enrolled 50 patients [7]. Furthermore, previous studies which were conducted by our research group [14,15], confirm the importance, relevance and possibility to investigate the personalized approach to the prescription of BZDs (and specifically diazepam) in such cohort of patients.…”
Section: Discussionsupporting
confidence: 91%
“…Diazepam is mainly metabolized via CYP2C19 and CYP3A4 to its major active metabolite, desmethyldiazepam. Recent studies revealed the effect of CYP2C19 and CYP3A4 genetic polymorphisms on the pharmacokinetics of BZDs [7][8][9][10]. The differences in the activity of these enzymes are genetically determined.…”
Section: Introductionmentioning
confidence: 99%